Expression and characterization of a novel alginate-binding protein: A promising tool for investigating alginate. (15th October 2020) - Mei, Xuanwei; Chang, Yaoguang; Shen, Jingjing; Zhang, Yuying; Xue, Changhu
Highlights: A novel alginate-binding protein ABP_Wf was discovered from an alginate PUL. The binding capacity of ABP_Wf was qualitatively and quantitatively characterized. It binds to alginate, not to pectin, glycosaminoglycans, laminarin and fucoidans. Its alginate-binding capacity is attributed to the constituent CBM16 domain. It can be used in semi-quantitative analysis and in situ visualization of alginate. Abstract: Alginate is a commercially important polysaccharide widely applied in various industries. Carbohydrate-binding proteins could be utilized as desirable tools in the investigation and further applications of polysaccharides. Few alginate-binding proteins have hitherto been characterized and reported. In the present study, a novel alginate-binding protein ABP_Wf, consisting of two "orphan" carbohydrate-binding modules, was cloned from a predicted alginate utilization locus of marine bacterium Wenyingzhuangia funcanilytica, and expressed in Escherichia coli . ABP_Wf exhibited a specific binding capacity to alginate, and the association constant ( Ka ) and affinity ( KD ) were 1.94 × 10 3 M −1 s −1 and 1.16 × 10 −6 M. It was confirmed that the binding capacity of ABP_Wf to alginate is attributed to its constituent CBM16 domain rather than the CBM44 domain. The potentials of ABP_Wf in the semi-quantitative detection and the in situ visualization of alginate were evaluated, which implied that ABP_Wf could be served as a promising tool for investigating alginate.